Reflection on Ethical Cyberspace: An Ethics of Human Development and Capabilities Approach - Delez, Rodney Timothy (Social Sciences and Development Review, 2013)
The internet is a technology that permeates in the habitat of the modern man of today. It carries the power to change and mold the way man lives and acts. It can produce many other effects as well out of it that may not have been thought of before. To consider that man as a being in relation to others carries the distinction of values shared and dissipated to everyone. And the internet is a medium where communication and interaction of one being to another do happen. Such a development need not produce a worsening of man’s wellbeing and flourishing. In fact, the internet, if put to an ethical use and regulated by reflexive minds, can produce a powerful tool for progress and development, not only on economistic terms, but on human development as well. As we strive to preserve humanity that we would want it to normatively become, we actively pursue an ethical development of cyberspace and its derivatives thereof.
Keywords: ethics; ethical cyberspace; reflection on technology; ethical use of technology